Implementation of Free Nutritious Meal Program to Promote Students' Healthy Lifestyles - Dhistanta Rangga Nardika; Muh Isna Nurdin Wibisana; Dian Ayu Zahraini (Universitas Negeri Semarang, 2026)
This study aims to analyze the implementation and impact of the free nutritious meal program on the development of a healthy lifestyle among students at SMP Negeri 39 Semarang. This study used a mixed method approach to comprehensively understand the study, combining quantitative and qualitative approaches. Quantitative data were obtained through questionnaires distributed to students, while qualitative data were collected through observations and interviews with relevant parties. Quantitative data were analyzed using statistical tests with the help of SPSS, while qualitative data were analyzed descriptively. The results showed that the implementation of the MBG program was well-structured and well-organized, starting from the signing of the MoU to the distribution of food, which was carried out in a disciplined manner. This program had a positive impact on healthy eating habits and student discipline. The analysis showed a very strong and significant relationship between the MBG program and the development of a healthy lifestyle among students, with a correlation coefficient of 0.941. Supporting factors included school support, collaboration with SPPG, student enthusiasm, and parental support. Obstacles found included limited learning time and menu incompatibility with students' tastes. Therefore, improvements in time management, increased menu variety, and ongoing nutrition education are needed. Thus, the MBG program has a positive influence on the formation of a healthy lifestyle among students at SMP Negeri 39 Semarang